Upaya Meningkatkan Kemampuan Siswa Memahami Jenis-Jenis Hewan Langkah Dengan Menggunakan Media Gambar Pada Siswa Kelas VIC SD Negeri 002 Rambah - Elziati Elziati (JURNAL PENDIDIKAN ROKANIA, 2018)
Research aim to improve science learning outcomes about the material species of rare animals approaching extinction by using the image media on students of class Vic SDN 002 Rambah, Pasir Pengaraian Kabupaten Rokan Hulu. The subjects of the study were students of class VIc SDN 002 Rambah which amounted to 23 students. Action research iscarried out in 2 cycles. Data collection in this study using test and observation mentods. The results showed that learning by using the image media can improve the learning outcomes of scinse. On average prasiklus yield 68,26, average cycle evaluation I of 71,85, average evaluation of cycle II of 78, 36. It shows an increase in value from prasiklus to cycle II of 10,1